Respuesta del arroz de riego al nitrógeno, fósforo y potasio en suelos del Norte del Cesar y la Guajira. - Rosero Morán, M.J.; Giraldo, J.I.; Quintero Durán, R. (Instituto Colombiano Agropecuario, 2018)
Arroz-Oryza sativa